Automation and Income Inequality in Europe - Karina Doorley; Jan Gromadzki; Piotr Lewandowski; Dora Tuda; Philippe Van Kerm (Institute of Labor Economics (IZA), 2023)
We study the effects of robot penetration on household income inequality in 14 European countries between 2006–2018, a period marked by the rapid adoption of industrial robots. Automation reduced relative hourly wages and employment of more exposed demographic groups, similarly to the results for the United States. Using robot-driven wage and employment shocks as input to the EUROMOD microsimulation model, we find that automation had minor effects on income inequality. Household labour income diversification and tax and welfare policies largely absorbed labour market shocks caused by automation. Transfers played a key role in cushioning the transmission of these shocks to household incomes.
Keywords: J24; O33; J23; 330; robots; automation; tasks; income inequality; wage inequality; microsimulation